Monitoring the agri-food system in Myanmar: Understanding the rapid price increase of vegetable oils - Myanmar Agriculture Policy Support Activity (International Food Policy Research Institute, 2022)
This Research Note presents the results from an assessment of the evolution of vegetable oil prices in Myanmar. Vegetable oils are an important product in the diet of Myanmar consumers and high food inflation in the country - 19 percent between December 2022 compared to December 2021 (MAPSA 2022) - is partly explained by substantial price increases for vegetable oils. The purpose of this analysis is to provide insights on what might explain the price increases of vegetable oils in local markets. To do this assessment, we rely on different secondary data sources as well as MAPSA’s food vendor survey conducted in March 2022 in all states/regions of the country. In this survey, 419 food vendors provided information on the sale of vegetable oils. We also rely on information from key informants in the sector.